Simbol Bunga Melati: Revolusi dan Perubahan di Tunisia - Romli, Hasbiyallah (IAIN Syekh Nurjati Cirebon, 2023)
This research aims to explore the democracy transition in Tunisia after the Arab Spring. The research method used is qualitative descriptive, with data collected through a literature review approach. The research findings indicate that after the Jasmine Revolution, Tunisia underwent significant transformations in various sectors, including politics, economics, and social aspects. Politically, there was a shift towards a more democratic system, with the formation of a new constitution in 2014 and elections that established an inclusive government. Economic issues, such as high unemployment rates and economic inequality, remained significant and needed to be addressed. Additionally, Tunisian society demanded social justice and efforts to combat corruption.In conclusion, the Jasmine Revolution in Tunisia not only had an impact on Tunisia itself but also served as an inspiration for the broader wave of Arab revolutions across the region. This event provided momentum for the advocacy of civil, political, and social rights in other Arab countries, with hopes for a more extensive positive change in Arab societies.